2012
DOI: 10.1029/2012ja017604
|View full text |Cite
|
Sign up to set email alerts
|

Strong longitudinal difference in ionospheric responses over Fortaleza (Brazil) and Jicamarca (Peru) during the January 2005 magnetic storm, dominated by northward IMF

Abstract: [1] In this study we investigate the response of the equatorial F layer to disturbance zonal electric field associated with IMF (interplanetary magnetic field) variations dominated by a strong northward Bz episode during the magnetic storm that occurred on 21 January, 2005. We compared the results obtained from Digisondes operated at Fortaleza, Brazil (Geogr. 3.9 S, 38.45 W; dip angle: À11.7 ) and Jicamarca, Peru (Geogr. 12.0 S, 76.8 W; dip angle: 0.64 ). A large auroral activity (AE) intensification that occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 51 publications
(70 reference statements)
1
27
0
Order By: Relevance
“…In addition, the F layer at Fortaleza descends during the main phase (19:40 UT/16:40 LT on 21 January), but this feature was not observed at Jicamarca. The longitudinal differences found by Santos et al [2012] are interesting, but we do expected some difference when we compare ionospheric data from equatorial region (Jicamarca) and low latitude (Fortaleza) during geomagnetic quiet and disturbed periods. On the other hand, the present investigation very clearly shows the EIA east-west differences using two chains of 10 GPS stations, each (from equator to beyond EIA crest).…”
Section: Discussionmentioning
confidence: 84%
“…In addition, the F layer at Fortaleza descends during the main phase (19:40 UT/16:40 LT on 21 January), but this feature was not observed at Jicamarca. The longitudinal differences found by Santos et al [2012] are interesting, but we do expected some difference when we compare ionospheric data from equatorial region (Jicamarca) and low latitude (Fortaleza) during geomagnetic quiet and disturbed periods. On the other hand, the present investigation very clearly shows the EIA east-west differences using two chains of 10 GPS stations, each (from equator to beyond EIA crest).…”
Section: Discussionmentioning
confidence: 84%
“…Many studies have investigated the influence of these disturbance electric fields on the vertical drift and related phenomena of the equatorial ionosphere, including the equatorial ionization anomaly (EIA), plasma structuring leading to bubble irregularities, equatorial electrojet current system, etc. [e.g., Mannucci et al , ; Abdu et al , , , , ; Batista et al , , ; Kikuchi et al , ; Santos et al , ; Sastri et al , ; Sobral et al , , ; Tsurutani et al , ]. The effect of storm time penetration zonal electric field to produce large vertical plasma drift, or superfountain, and dayside total electron content enhancement with resulting EIA intensification was reported by Mannucci et al [] and Tsurutani et al [].…”
Section: Introductionmentioning
confidence: 93%
“…The same pattern was analyzed using a large data set obtained from TOPEX TEC measurements, and it was found to exist not only during magnetically quiet periods but also during disturbed periods when there were other disturbance sources for zonal electric fields [ Scherliess et al , ]. Santos et al [] reported a large longitudinal difference in zonal disturbance electric fields during a magnetic storm between Fortaleza, Brazil, and Jicamarca, Peru, which were separated by 30° longitude or 2 h in local time.…”
Section: Storm‐induced Plasma Streammentioning
confidence: 99%